Effect of Cell Wall Ductility and Toughness on Compressive Response and Strain Rate Sensitivity of Aluminium Foam. (2nd May 2019) - Byakova, Alexandra; Gnyloskurenko, Svyatoslav; Vlasov, Andrey; Semenov, Nikolay; Yevych, Yan; Zatsarna, Oleksandra; Danilyuk, Vladimir
Abstract : The study presents the effect of cell wall ductility and toughness on the compressive behaviour of closed-cell Al foams under static and dynamic loading and localised deformation by indentation. Two kinds of Al alloys including relatively ductile AlSiMg alloy and high-strength AlZnMg alloy, which comprises a great amount of brittle eutectic domains, were used as matrix materials. Both kinds of Al foams were fabricated via newly developed melt processing using the CaCO3 -foaming agent without Ca additive. Mechanical behaviour of Al foams under quasi-static compression and indentation was examined and compared with that performed under dynamic loading using direct impact tests. Characteristic events revealed in deformation patterns of Al foams at quasi-static compression were also monitored with the CCD camera. Significant differences in stress-strain response and strain rate sensitivity of Al foams arose from the difference in the microstructure, and hence, ductility and toughness of the cell wall material were investigated and discussed.